Governance, maternal well-being and early childhood caries in 3-5-year-old children. - Folayan, Morenike Oluwatoyin; El Tantawi, Maha; Vukovic, Ana; Schroth, Robert J; Alade, Micheal; Mohebbi, Simin Z; Al-Batayneh, Ola B; Arheiam, Arheiam; Amalia, Rosa; Gaffar, Balgis; Onyejaka, Nneka Kate; Daryanavard, Hamideh; et al. (BMC Oral Health., 2024)
8p.